HLA and smoking in prediction and prognosis of small cell lung cancer in autoimmune Lambert-Eaton myasthenic syndrome. - Wirtz, P; Willcox, N; van der Slik, A; Lang, B; Maddison, P; Koeleman, B; Giphart, M; Wintzen, A; Roep, B; Verschuuren, J (2005)
Patients with small cell lung cancer (SCLC) survive longer if they have the antibody-mediated Lambert-Eaton myasthenic syndrome (LEMS), making this autoimmune disorder a prototype disease for studying cancer immunosurveillance. Patients with nontumor LEMS (NT-LEMS) never develop SCLC but are otherwise indistinguishable clinically. Therefore, we have compared immunogenetic factors in SCLC-LEMS and NT-LEMS and studied their role in the pathogenesis of LEMS and survival from SCLC. In 48 British and 29 Dutch Caucasian LEMS patients, we studied clinical symptoms, antibody titers, HLA types and alleles at six nearby located microsatellite loci. Highly significant associations were found in NT-LEMS, which appeared strongest with HLA-B8, but also involved HLA-DQ2, -DR3 and six flanking microsatellite alleles. SCLC-LEMS patients were not different from controls. Smoking was a strong predictor of SCLC. In contrast, HLA-B8 positivity correlated with a decreased risk of SCLC even among the smokers. Moreover, in SCLC-LEMS patients, HLA-B8 positivity correlated with prolonged survival after LEMS onset. We propose that two distinct immunopathogenetic routes can lead to one clinically and serologically indistinguishable autoimmune myasthenic syndrome. HLA-DR3-B8 is strongly associated with LEMS in nontumor patients only. In other LEMS patients, SCLC apparently provides a powerful autoimmunogenic stimulus that overrides HLA restrictions in breaking tolerance to calcium channels. Moreover, negativity for HLA-B8 combined with smoking behavior points more strongly to an underlying SCLC and predicts a worse prognosis in SCLC-LEMS patients.